The verbal aggression in modern media (Eurasian Journal of Philology Science and Education, 2016)
This article addresses the issue of verbal aggression in the modern media. We formulate a modern print media analysis of texts. The author notes that, along with descriptive and expressive means that perform positive tasks, periodically there are many publications with a negative valuation vocabulary injected negative emotions. Based on this analysis in the article are numerous examples taken from contemporary newspapers and magazines. The examples of the use by journalists of different images on the topic. The materials used in the paper are recommendations for those interested in linguistic methods, style, structure of modern journalism.
Keywords: aggression; verbal aggression; media; text analysis